2020
DOI: 10.1002/slct.202001965
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Adsorption of Heavy Metal Ions by A Novel AO‐PAN‐g‐Chitosan/Fe3O4 Composite

Abstract: In this study, a novel amidoxime‐based magnetic adsorbent (AO‐PAN‐g‐Chitosan/Fe3O4) was prepared by grafting acrylonitrile onto the surface of chitosan (CS) and magnetic Fe3O4 composite, followed by amidoximation. The magnetic adsorbents were characterized by infrared spectroscopy (FT‐IR) and X‐ray diffraction (XRD). The adsorption properties of the magnetic adsorbents for heavy metal ions in aqueous solutions were investigated under different conditions, including pH, contact time, and initial concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Li et al prepared a new type of amidoxime-based magnetic adsorbent. 150 Under the optimal conditions, the maximum adsorption efficiency for Ni( ii ) ions is 32.68 mg g −1 . Dong et al synthesized magnetic phosphorylated chitosan composite (P-MCS).…”
Section: Application Of Modified Magnetic Chitosan Materials In Heavy...mentioning
confidence: 96%
“…Li et al prepared a new type of amidoxime-based magnetic adsorbent. 150 Under the optimal conditions, the maximum adsorption efficiency for Ni( ii ) ions is 32.68 mg g −1 . Dong et al synthesized magnetic phosphorylated chitosan composite (P-MCS).…”
Section: Application Of Modified Magnetic Chitosan Materials In Heavy...mentioning
confidence: 96%
“…It has been observed that a material exhibits remarkable reproducibility and reusability, as evidenced by its ability to undergo five adsorption-desorption cycles without experiencing any notable decline in its adsorption capacity for Cu(II) and Ni(II) ions [146]. Another study reported that Fe3O4-graphene oxide-chitosan removes 96.73 % of Zn(II) in 38 min, with adsorption quantity 386.92 mg•g −1 [147].…”
Section: Magnetic Chitosan Compositementioning
confidence: 99%
“…Chitosan is a typical representative of biopolymers, which is derived from chitin and is a representative example of biopolymers [75]. Due to its strong biocompatibility, biodegradability, and abundant functional groups (-NH 2 , -OH, -COOH), chitosan is often used for functionalized assembly with nano-Fe 3 O 4 [83][84][85]. A complexation effect easily occurs between chitosan and nano-Fe 3 O 4 particles, facilitated by the nitrogen atoms in the amine groups of the chitosan sharing lone electron pairs with divalent or trivalent iron on the surface of the nano-Fe 3 O 4 .…”
Section: Ectopic Assembly With Biopolymersmentioning
confidence: 99%